2020
DOI: 10.1186/s12913-020-05531-9
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of subnational disparities in antenatal care utilisation: a spatial analysis of demographic and health survey data in Kenya

Abstract: Background: The spatial variation in antenatal care (ANC) utilisation is likely associated with disparities observed in maternal and neonatal deaths. Most maternal deaths are preventable through services offered during ANC; however, estimates of ANC coverage at lower decision-making units (sub-county) is mostly lacking. In this study, we aimed to estimate the coverage of at least four ANC (ANC4) visits at the sub-county level using the 2014 Kenya Demographic and Health Survey (KDHS 2014) and identify factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 61 publications
(83 reference statements)
4
22
0
Order By: Relevance
“…37 The uptake of ANC services among married women was higher compared with women living alone. This finding is consistent with the studies conducted in Ethiopia, 15 Kenya, 32 Rwanda 38 and Bangladesh. 35 The higher ANC uptake could be attributed to the psychological and economic support obtained from their husbands, plannedness and desirability of their pregnancy, and the societal acceptability and support of their pregnancy state when compared with their unmarried women.…”
Section: Discussionsupporting
confidence: 93%
“…37 The uptake of ANC services among married women was higher compared with women living alone. This finding is consistent with the studies conducted in Ethiopia, 15 Kenya, 32 Rwanda 38 and Bangladesh. 35 The higher ANC uptake could be attributed to the psychological and economic support obtained from their husbands, plannedness and desirability of their pregnancy, and the societal acceptability and support of their pregnancy state when compared with their unmarried women.…”
Section: Discussionsupporting
confidence: 93%
“…Our results suggest that disparities in the spatial extents of APOs may have been driven by demand-side barriers and supply-side challenges, with low-resource counties disproportionately vulnerable to adverse outcomes. Recent studies highlight a heterogenous timing and coverage of ANC4 across sub-counties in Kenya, with poorer/rural sub-counties in northern Kenya exhibiting low coverage levels [ 50 , 51 ]. The current guidance from the WHO suggesting at least four comprehensive and targeted visits [ 16 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings did not qualitatively vary in a statistically significant manner, at the 5 or 10% level, on limiting our analysis to violent or non-violent conflict events, varying the facility catchment area radius, or adjusting for confounders. The determinants of gaps in access to high-quality ANC and other maternal health services are multifaceted, including poverty, lower educational levels, and physical distance from health facilities (35)(36)(37). In this study, we have demonstrated that conflict is also an important determinant of the quality of ANC that women receive in this context.…”
Section: Discussionmentioning
confidence: 68%
“…The determinants of gaps in access to high-quality ANC and other maternal health services are multifaceted, including poverty, lower educational levels, and physical distance from health facilities ( 35 37 ). In this study, we have demonstrated that conflict is also an important determinant of the quality of ANC that women receive in this context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation